PEMILIHAN PROGRAM PENGENTASAN KEMISKINAN MELALUI PENGEMBANGAN MODEL PEMBERDAYAAN MASYARAKAT DENGAN PENDEKATAN SISTEM - Sutikno, Sutikno; Soedjono, Eddy Setiadi; Rumiati, Agnes Tuti; Trisunarno, Lantip (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2010)
This research aims to compile the programs for poverty alleviation by community empowerment model and review the determination program as effectiveness evaluation poverty alleviation program which still canât be worked properly. Stages the compiling program of poverty alleviation is mapping the socioeconomic conditions of the poor, basic infrastructure conditions, socio-cultural issues, and potential issues; identifying the hopes and predicting the economic development opportunities; creating the poverty alleviation program by SWOT analysis and planning implementation program with KPD. Based on the result of SWOT and scoring analysis, the selected programs are training and assistance, the establishment of cooperative saving and loans, clean water for poor households, rural development with the utilization of clean water, household waste management, and package education program A, B, and C.